(untitled) (Economics and region, 2016)
In the article is reasoned the place of organic farming in the economies of member states. The classification of EU member states is made on the basis of cluster analysis, taking into account the role of organic agriculture in their economies, on the criteria of share of rural population, share of organic farmland and share of employed in organic agriculture. Evaluation has shown that organic agriculture is more important for Austria and some of the relatively less developed EU countries. The aim of such countries, as well as for Ukraine, is the transition to a more efficient organic agriculture, which will provide an adequate level of income for the population and the rural development.